2021
DOI: 10.3390/ijerph18010351
|View full text |Cite
|
Sign up to set email alerts
|

Time-Varying Insomnia Symptoms and Incidence of Cognitive Impairment and Dementia among Older US Adults

Abstract: There is conflicting evidence regarding the association between insomnia and the onset of mild cognitive impairment (MCI) or dementia. This study aimed to evaluate if time-varying insomnia is associated with the development of MCI and dementia. Data from the Health and Retirement Study (n = 13,833) from 2002 to 2014 were used (59.4% female). The Brief Insomnia Questionnaire was used to identify insomnia symptoms which were compiled in an insomnia severity index, ranging from 0 to 4. In analysis, participants’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The above study also found that over the 4.9 years of follow-up, women with the poorest sleep efficiency had 1.5 greater odds of acquiring MCI or dementia, whereas women with longer sleep latencies had 1.4 greater odds of cognitive impairment [12]. Insomnia is characterized by trouble falling asleep, waking up during the night, waking up early and not being able to fall back asleep, and non-restorative sleep [2]. One study after controlling for other demographics/variables/factors showed that for each extra insomnia symptom, there was a 5% increased risk of incident MCI (HR = 1.05; 95% CI: 1.04-1.06) and dementia (HR = 1.05; 95% CI: 1.03-1.06) after 12 years of follow-up [2].…”
Section: Types Of Sleep Disorders In MCImentioning
confidence: 74%
See 2 more Smart Citations
“…The above study also found that over the 4.9 years of follow-up, women with the poorest sleep efficiency had 1.5 greater odds of acquiring MCI or dementia, whereas women with longer sleep latencies had 1.4 greater odds of cognitive impairment [12]. Insomnia is characterized by trouble falling asleep, waking up during the night, waking up early and not being able to fall back asleep, and non-restorative sleep [2]. One study after controlling for other demographics/variables/factors showed that for each extra insomnia symptom, there was a 5% increased risk of incident MCI (HR = 1.05; 95% CI: 1.04-1.06) and dementia (HR = 1.05; 95% CI: 1.03-1.06) after 12 years of follow-up [2].…”
Section: Types Of Sleep Disorders In MCImentioning
confidence: 74%
“…Chronic insomnia has been linked to a slew of negative health outcomes, including a greater risk of high blood pressure, diabetes, obesity, depression, myocardial ischemia, and stroke, as well as a higher chance of cognitive decline and dementia [2]. General sleep alterations observed in healthy older people are increased nocturnal awakenings leading to fragmentation of sleep and decreased daily sleep duration due to equal reductions in both rapid eye movement (REM) and NREM.…”
Section: Types Of Sleep Disorders In MCImentioning
confidence: 99%
See 1 more Smart Citation
“…Several smaller community‐based studies suggest a link between sleep disorders and dementia. For instance, insomnia has been suggested to increase the risk of mild cognitive impairment (MCI) and AD [ 6 ] as well as all‐cause dementia by 5% [ 7 ]. Sleep‐disordered breathing has been linked to increased risk of MCI and AD [ 8 , 9 ] and may cause earlier cognitive decline to MCI and AD by around 10 years compared to those without [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While approximately 30%–33% of adults experience symptoms of insomnia, only 6%–10% of adults meet diagnostic criteria for the full insomnia syndrome, which requires sleep difficulties at least 3 nights weekly for at least 3 months, with adverse consequences for daytime functioning 2,3 . The insomnia syndrome, insomnia symptoms, and short sleep duration throughout middle and older adulthood all have been shown to increase dementia risk 4–6 . Further, excessively short (≤4 h) sleep duration among older adults is associated with accelerated cognitive decline, 7 and <6 h of nightly sleep increases older adults' risk for conversion from cognitively normal status to Mild Cognitive Impairment i (MCI; i.e., cognitive decline with preserved functional abilities to execute daily tasks, such as driving and managing medications and finances) 8,9 .…”
Section: Introductionmentioning
confidence: 99%